PENGAWASAN SISTEM PEMBUANGAN SAMPAH DI KOTA PEKANBARU - Roy Hidayat; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Waste control is an action taken in establishing rules relating to activities to assess or correct errors that occur, especially in waste management. This temporary waste management is seen as the sole responsibility of the government. The community plays a more role only as the party being served, because they feel that it is enough just to pay the garbage retribution fee so that further handling is the responsibility of the government. Government management efforts in planning, implementing and monitoring so that programs / activities related to waste can achieve cleanliness and beauty in Pekanbaru City, but these efforts have not been supported by the availability of facilities and infrastructure related to the waste transportation unit, causing the problem of accumulating waste. The purpose of this study is to analyze the supervision of the garbage disposal system in Pekanbaru City and its obstacles. This type of research is qualitative research with a phenomenological approach. The informants in this study were the Head of Pekanbaru City Waste Handling and Final Processing Section, Supervisors, Foremen and Muara Fajar TPA Workforce. Data collection techniques are interviews, observation and documentation. This study concludes that the implementation of monitoring the garbage disposal system in Pekanbaru City has not been optimally implemented. It is known from the existence of problems related to the waste that is disposed of in the Muara Fajar TPA which cannot be processed directly, so that the waste accumulates and cannot be processed effectively anymore. The occurrence of this problem is also from the lack of direct supervision by the relevant agencies to find out the problems that occur at the TPA. Inhibiting factors in the implementation of the garbage processing system at Muara Fajar's final disposal site (TPA) in Pekanbaru City is the lack of inadequate human resources in terms of quantity and quality, then infrastructure that is not supported by maintenance and repair activities of equipment, so that processing garbage at the Muara Fajar TPA, Pekanbaru City is hampered due to the condition of damaged equipment.  Keywords: Implementation, Supervision, Final Processing Place